Islam, politics and change the Indonesian experience after the fall of Suharto - Dijk, Kees van 1946-; Kaptein, Nicolaas J. G. 1956-; Suharto 1921-2008 (Leiden Leiden University Press, 2016)
After violent protests across the country had forced President Suharto to step down in 1998, Indonesia successfully made the transition from an authoritarian state to a democracy. For the first time in forty years Islamic parties and organizations - including some inspired by the Egyptian Muslim Brotherhood - were free to propagate their ways of thinking. The new government also succeeded in negotiating an end to a separatist rebellion in Aceh, making the province the only region in Indonesia permitted to draft its own Islamic legislation. In this book Indonesian scholars affiliated with Islamic universities as well as Dutch researchers investigate what has happened since the transition. They explore what the consequences are of the growing influence of orthodoxy and radicalism, which - while already visible prior to 1998 - has only grown stronger. How did political and religious relations change? How were the lives of women and their legal position affected? Furthermore, what are the ramifications for religious minorities?
Keywords: Islam and politics -- Indonesia -- History -- 21st century; Indonesia -- Politics and government -- 1998-